Sex-Specific Retinal Anomalies Induced by Chronic Social Defeat Stress in Mice - Arsenault, Eric; Lavigne, Andrée-Anne; Mansouri, Samaneh; Gagné, Anne-Marie; Francis, Kimberley; Bittar, Thibault P.; Quessy, Francis; Abdallah, Khaled; Barbeau, Annie; Hébert, Marc; Labonté, Benoit (Frontiers in Behavioral Neuroscience, 2021)
Major depressive disorder (MDD) is one of the most common consequences of chronic stress. Still, there is currently no reliable biomarker to detect individuals at risk to develop the disease. Recently, the retina emerged as an effective way to investigate psychiatric disorders using the electroretinogram (ERG). In this study, cone and rod ERGs were performed in male and female C57BL/6 mice before and after chronic social defeat stress (CSDS). Mice were then divided as susceptible or resilient to stress. Our results suggest that CSDS reduces the amplitude of both oscillatory potentials and a-waves in the rods of resilient but not susceptible males. Similar effects were revealed following the analysis of the cones b-waves, which were faster after CSDS in resilient mice specifically. In females, rods ERGs revealed age-related changes with no change in cone ERGs. Finally, our analysis suggests that baseline ERG can predict with an efficacy up to 71% the expression of susceptibility and resilience before stress exposition in males and females. Overall, our findings suggest that retinal activity is a valid biomarker of stress response that could potentially serve as a tool to predict whether males and females will become susceptible or resilient when facing CSDS.